1996
DOI: 10.1007/bf01969706
|View full text |Cite
|
Sign up to set email alerts
|

A model for the mechanism of precise integration of a microinjected transgene

Abstract: A unique transgenic mouse line has undergone transgene integration in a very precise fashion. The phenotype displayed by mice of the line followed the predicted inheritance patterns for X-linked transgene insertion which has been confirmed. In order to investigate the mechanism of integration the DNA sequence of the transgene and cellular junctions have been determined. A comparison between wild type and transgenic mutant sequences at the site of insertion revealed that there was no loss or rearrangement of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Such findings are a recurrent theme: many other investigators have found Topo I consensus sequences, and other sequences such as Escherichia coli CHI element and minisatellite sequences, near transgene-chromosome junctions. 43,44,59,94,95 It has been demonstrated that integration of a circular bent DNA-containing vector preferentially occurs at the bent site, while bent DNA structures are often found at illegitimate recombination junctions and rearrangement breakpoints. 76 This suggests that such bent DNA sites in the genome (which are numerous) might be involved in integration.…”
Section: Illegitimate Integration Sites Are Not Totally Randommentioning
confidence: 99%
See 2 more Smart Citations
“…Such findings are a recurrent theme: many other investigators have found Topo I consensus sequences, and other sequences such as Escherichia coli CHI element and minisatellite sequences, near transgene-chromosome junctions. 43,44,59,94,95 It has been demonstrated that integration of a circular bent DNA-containing vector preferentially occurs at the bent site, while bent DNA structures are often found at illegitimate recombination junctions and rearrangement breakpoints. 76 This suggests that such bent DNA sites in the genome (which are numerous) might be involved in integration.…”
Section: Illegitimate Integration Sites Are Not Totally Randommentioning
confidence: 99%
“…It appears that exogenous DNA generally integrates at one, or very few, site(s) in the recipient genome, but often in multiple copies showing the presence of 1-6 bp of microhomology or slight degrada- Illegitimate DNA integration H Würtele et al tion or addition of nucleotides at transgene-transgene junctions. [41][42][43][44][45][46][47] The NHEJ activities capable of circularizing and concatemerizing extrachromosomal DNA have been suggested to account for randomly oriented transgene arrays, while the frequent appearance of tandem arrays comprised of direct repeats is best explained by homologous recombination between circular and linear molecules before or during the integration process. 41,42 The organization and quantity of integrated DNA appear to vary according to cell type.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, as described in our another report, the p(B1/2) 2 ␤geo-injected blastocyst embryos showed much higher levels of ␤-gal expression compared with the p␤geo-injected control embryos. 2 It is generally accepted that the frequency of random integration into a genome is highly affected by the sequences of transgene ends (26,37). In measuring the integration efficiency of SINE-flanked vectors by the microinjection experiment we excluded such potential bias by linearizing both control and SINE-tagged vectors with the ScaI restriction enzyme, which cuts both plasmids once within the ampicillin-resistant gene leaving the repetitive sequences positioned internally in the vectors.…”
Section: Discussionmentioning
confidence: 99%
“…Unusually for microinjected transgene integrations, the sequences on either side of the transgene insertion showed absolutely no rearrangements, nucleotide losses, or nucleotide additions compared to the wildtype locus and were found to be contiguous in wildtype murine DNA (McFarlane and Wilson, 1996). The genomic sequences immediately adjacent to the transgene insertion site were found to be unique and were used to map the disrupted locus by an interspecific backcross analysis (locus map nomenclature DXRib1/ DXPri1).…”
Section: Introductionmentioning
confidence: 99%